Home Treatment Compared to Initial Hospitalization in Normotensive Patients with Acute Pulmonary Embolism in the Netherlands: A Cost Analysis - Hendriks, Stephan V.; van den Hout, Wilbert B.; van Bemmel, Thomas; Bistervels, Ingrid M.; Eijsvogel, Michiel; Faber, Laura M.; Hofstee, Herman M. A.; van der Hulle, Tom; Iglesias del Sol, Antonio; Kruip, Marieke J. H. A.; Mairuhu, Albert T. A.; Middeldorp, Saskia; Nijkeuter, Mathilde; Huisman, Menno V.; Klok, Frederikus A.; for the YEARS Investigators (Thrombosis and Haemostasis, 2021)
Background Venous thromboembolism constitutes substantial health care costs amounting to approximately 60 million euros per year in the Netherlands. Compared with initial hospitalization, home treatment of pulmonary embolism (PE) is associated with a cost reduction. An accurate estimation of cost savings per patient treated at home is currently lacking.Aim The aim of this study was to compare health care utilization and costs during the first 3 months after a PE diagnosis in patients who are treated at home versus those who are initially hospitalized.Methods Patient-level data of the YEARS cohort study, including 383 normotensive patients diagnosed with PE, were used to estimate the proportion of patients treated at home, mean hospitalization duration in those who were hospitalized, and rates of PE-related readmissions and complications. To correct for baseline differences within the two groups, regression analyses was performed. The primary outcome was the average total health care costs during a 3-month follow-up period for patients initially treated at home or in hospital.Results Mean hospitalization duration for the initial treatment was 0.69 days for those treated initially at home (n = 181) and 4.3 days for those initially treated in hospital (n = 202). Total average costs per hospitalized patient were €3,209 and €1,512 per patient treated at home. The adjusted mean difference was €1,483 (95% confidence interval: €1,181–1,784).Conclusion Home treatment of hemodynamically stable patients with acute PE was associated with an estimated net cost reduction of €1,483 per patient. This difference underlines the advantage of triage-based home treatment of these patients.
Keywords: costs; home treatment; hospitalization; pulmonary embolism